Synergy of Digital Competence and Customer Co-Creation: MSME Product Innovation Strategy - Sihol Marito Br Siagian; Siska Ernawati Fatimah (Interdisciplinary Social Studies, 2026)
This study aims to analyze the effect of digital competence and customer co-creation on product innovation in culinary MSMEs in Cirebon City and its surrounding areas. The study uses a quantitative approach with an explanatory design and cross-sectional method. Data were collected through structured questionnaires from 312 culinary MSME actors determined using the Cochran formula. Data analysis was performed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method using SmartPLS 4.0 software. The results showed that digital competence and customer co-creation had a positive and significant effect on product innovation. Digital competence had a more dominant effect than customer co-creation. The coefficient of determination (R²) value of 0.836 indicates that 83.6% of product innovation variation can be explained by these two variables. This finding indicates that strengthening digital competence is a major factor in driving MSME product innovation, while customer involvement plays a supporting role in strengthening the innovation process to better suit market needs.